A PROFILE OF ONLINE COURSE STUDENT - L. V. Popova; N. N. Marfenin; P. L. Pekker (Высшее образование в России)
This article presents the results of a two-year study of massive open online courses (MOOC) «Modern Environmental Problems and Sustainable Development», which is effective since September 2015 on National Russian Platform «Open Education» in terms of learners' audience. A learner's profile is made on the basis of the conducted survey. According to the data collected, these are young women, who are interested in this subject and who are currently students or young specialists residing mainly in Moscow region. We found out that 9-11% of the learners, who were initially enrolled, have completed the course. These figures are similar to the ones collected by foreign researchers on the basis of analysis of MOOCs run in other countries. One of the reasons for subscribing to an online course given was the opportunity to enlarge knowledge. This fact would be meaningful for improving existing courses so that they not only provide new information but revise existing knowledge as well. The important factor that describes a rise in popularity of online course «Modern Environmental Problems and Sustainable Development» is the increase in the number of subscribers who live abroad in 2016.